Digitalization in Public Administration Services in Indonesia: Pseudo or Real Digitalization - Ira Patriani; Rahmat Salam; Nuphanudin Nuphanudin; Masriadi Masriadi; Ni Luh Yulyana Dewi (Universitas Dharma Wacana, 2022)
Indonesia has a plan to implement information and communication technology (ICT) across the vast majority of government functions and public service delivery systems. This is due to the expanding needs of the community, which necessitates that the government be able to deliver good and outstanding service. Previously, the government had implemented e-government, or digitalization of public service processes. However, implementation still requires improvement. It involves the methodical incorporation of innovation into ICT, which ensures bottom-up learning for a seamless digital transformation of public services. Therefore, the purpose of this study is to determine whether the digitalization of public services in Indonesia is a reality or only hype. This study employs a qualitative approach and descriptive methodologies. The study's findings indicate that the reality of digitalizing public services (e-government) is that there are still misconceptions and perspectives that need to be clarified. In general, digitization in public services in Indonesia is in the emerging and enhancing stage; only a tiny number have implemented the interactive setting, so based on the E-Government Development Index (EDGI), Indonesia is lagging among ASEAN countries. The obstacles in the implementation of e-government include low data integration, implementation of e-government, low competence of apparatus, etc., so a strategy is needed to develop digitization in public administration services.